Review on Public Key Cryptography Scheme-Based Performance Metrics - Jasmin Ilyani Ahmad; Roshidi Din; Mazida Ahmad (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Cryptography is a method used to establish secure data communication. The goal of cryptography is to send data to satisfy the criteria of confidentiality, data integrity, authentication and non-repudiation. In line with the goals, the performance metrics is the important evaluation criteria to be analyzed. This paper presents the review of performance metrics of Public Key Cryptography (PKC) that had been analyzed based on the PKC scheme from the previous researchers’ effort since the last four decades. It also displayed the research pattern in different performance metrics over the years. The aim of this paper is to identify the key performance metrics which addressed by the researchers in previous studies. Finally, the critical concern of this paper which shows the overall PKC performance metrics also presented in this paper.